Apple wine processing with different nitrogen contents - Alberti, Aline; Vieira, Renato Giovanetti; Drilleau, Jean Françoise; Wosiacki, Gilvan; Nogueira, Alessandro (My University, 2011)
The aim of this work was to evaluate the nitrogen content in different varieties of apple musts and to study the effect of different nitrogen concentrations in apple wine fermentation. The average total nitrogen content in 51 different apples juices was 155.81 mg/L, with 86.28 % of the values above 100 mg/L. The apple must with 59.0, 122.0 and 163.0 mg/L of total nitrogen content showed the maximum population of 2.05x 107; 4.42 x 107 and 8.66 x 107 cell/mL, respectively. Therefore, the maximum fermentation rates were dependent on the initial nitrogen level, corresponding to 1.4, 5.1 and 9.2 g/L.day, respectively. The nitrogen content in the apple musts was an important factor of growth and fermentation velocity.
Keywords: Apple juice fermentated; Fermentation rate; Cider; Yeast